The search for best practices : doing the right thing the right way - Reider, Rob, 1940- (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2015)
The book is geared to those interested in doing the right thing the right way in spite of organizational roadblocks. The book is a "how to" book to assist management and operations personnel to analyze their operations in a program of continuous improvements and on-going search for best practices so that each entity operates most economically, efficiently, and effectively--tied into why the entity is in existence in the first place. Best practice techniques assist the company in identifying its critical problem areas and treating the cause and not the symptom. With sensible business principles as the hallmark for the company's quest for best practices, the company can be clear as to the direction of movement and avoid merely improving poor practices or matching competitors' less than desirable practices--that is, being less inefficient than competitors. Clear business principles that make sense to all levels of the organization allow the company to identify and develop the proper best practices. In this manner, everyone in the organization is moving in the same desired direction-- and singing from the same songbook. The viruses that corrupt a business organization can be widespread and quite contagious. Nouveau quick fixes may be okay in the short term, but over the long haul the company needs to know what they are doing. If the company doesn't, some other company will.
Overview: knowing where you're going -- Customer service -- Cash conversion -- Corporate culture -- Organization structure -- Organizational atmosphere -- Organizational communications -- Management -- Personnel -- Operating systems -- Appendices -- About the author -- Other books by Rob Reider -- Index.
Part of: 2014 digital library.
Includes index.
Title from PDF title page (viewed on December 21, 2014).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Corporate culture; Industrial efficiency; Industrial management; best practices; communication systems; corporate culture; economies; efficiencies and effectiveness; management; operating systems; organizational atmosphere; organization structure; personnel; teamwork; Electronic books